The Effect of Coaching and Leadership Style on Employee Work Motivation at PT. ABC in Jakarta, Tangerang and Bekasi - Trifiana Tiodora; Hendra Achmadi; Wilson Bangun; Yohana F. C. P. Meilani (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the effect of coaching program and leadership style on employee motivation at PT XYZ, a retail company engaged in selling shoes and bags. The research method used is descriptive quantitative, with data collection through closed questionnaires distributed to 36 respondents who are employees of PT XYZ in Jakarta, Tangerang, and Bekasi. The sampling technique used was simple random sampling. The independent variables in this study are coaching and leadership style, while the dependent variable is employee motivation. Multiple regression analysis was conducted to see the effect of each variable on employee motivation, with data processing using SPSS version 20. The results showed that coaching and leadership style significantly influenced employee motivation, with a percentage of positive responses to coaching of 87.7% and to leadership style of 83.8%. The conclusion of this study is that the coaching program run by the company has succeeded in increasing employee motivation, and the leadership style applied is able to provide clear direction and support the achievement of company targets. The combination of these two factors has a positive impact on employee performance and motivation at PT XYZ.